Refractory Ventricular Tachycardia Storm: A case report and review of literature - Navjyot Kaur (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Ventricular tachycardia (VT) storm continues to be an important challenge for the cardiologists all over the globe. VT storm usually occurs in a structurally diseased heart with low left ventricular ejection fraction (LVEF) but may also occur in patients with arrhythmic syndromes like long QT syndrome, Brugada syndrome and catecholaminergic polymorphic VT who have structurally normal heart. Despite its life threatening consequences, the guidelines and literature regarding management of incessant VT is sparse. Here we present a middle age male who presented with scar related refractory VT. Unfortunately we lost the patient; but this case highlights the diffi culty and challenges faced in management of hemodynamically unstable VT storm.